1996
DOI: 10.1046/j.1365-2133.1996.d01-1051.x
|View full text |Cite
|
Sign up to set email alerts
|

Acrodermatitis chronica atrophicans in an 11-year-old girl

Abstract: We report a case of acrodermatitis chronica atrophicans in an 11-year-old girl living in an area endemic for Lyme borreliosis. The diagnosis was first made on the basis of clinical, histopathological and serological findings. Moreover, Borrelia burgdorferi-specific DNA was amplified from lesional skin by polymerase chain reaction. Intravenous treatment with ceftriaxone (2 g once daily) for 2 weeks was initiated. The skin changes clearly responded to the therapy, and Borrelia burgdorferi-specific gene segments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
1
2

Year Published

1999
1999
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 20 publications
0
5
1
2
Order By: Relevance
“…The 22% BL cases diagnosed in our study together with the previously reported 14% BL cases of children with skin manifestations (22) and the 7% BL cases of all children with LB (9) indicate that BL is seen more frequently in children than in adults, in which BL accounts for only 2% of all LB cases (9). In contrast, ACA is an extreme rarity in children with only 11 described cases (22,(29)(30)(31)(32)(33)(34)(35). In adults, ACA has an estimated prevalence of 1-2% among all LB patients with skin manifestations and preferentially affects elderly people in Europe (11).…”
Section: Discussioncontrasting
confidence: 42%
“…The 22% BL cases diagnosed in our study together with the previously reported 14% BL cases of children with skin manifestations (22) and the 7% BL cases of all children with LB (9) indicate that BL is seen more frequently in children than in adults, in which BL accounts for only 2% of all LB cases (9). In contrast, ACA is an extreme rarity in children with only 11 described cases (22,(29)(30)(31)(32)(33)(34)(35). In adults, ACA has an estimated prevalence of 1-2% among all LB patients with skin manifestations and preferentially affects elderly people in Europe (11).…”
Section: Discussioncontrasting
confidence: 42%
“…[2][3][4] Chronic venous insufficiency is a very rare event in children and occurs almost exclusively in high-risk situations, such as the presence of venous malformations (eg, KlippelTrenaunay syndrome), congenital venous valvular aplasia of the lower extremities, congenital heart disease, or as postthrombotic complications of central venous lines in the upper extremity. 9,21 To our knowledge, the patient described in this report is only the fifth well-established case of childhood ACA published.…”
Section: Discussionmentioning
confidence: 99%
“…1 To our knowledge, only 4 well-established cases of ACA in childhood have been described. [2][3][4] It is important to diagnose and treat ACA as promptly as possible because expansion of skin changes, irreversible damage of epidermal and dermal structures, and extracutaneous signs and symptoms occur in the vast majority of patients after a longer disease duration. 1,5,6 ACA has many features that overlap with those of chronic venous insufficiency, 7 the advanced stage of incompetence of the venous system of the legs that is clinically characterized by varicose veins, bluish-red discoloration, edema, chronic inflammation of the dermis and subcutis with secondary eczema, hyperpigmentation, dermatosclerosis, and leg ulcers.…”
mentioning
confidence: 99%
“…Although LB is frequently observed in childhood in Europe and the U.S.A., 14 the majority of children do not present skin lesions, but acute articular and neurological disorders. Skin involvement in childhood LB usually manifests as borrelial lymphocytoma located on the ear, the nipple or the scrotum, or as EM, with the head and neck region being predominantly affected 15 . ACA, however, seems to be very rare in childhood.…”
Section: Discussionmentioning
confidence: 99%